Implementasi MAUT Dan ROC Untuk Menentukan Pemenang Wisata Rohani Tahunan Di BTPN Putri Hijau Medan - Onella, Nevin (Management of Information System Journal, 2023)
Bank BTPN stands for Bank Tabungan Pensiunan Nasional which focuses on the mass market segment which consists of retirees, micro, small and medium enterprises (MSMEs), productive underprivileged communities, consuming class segment, and the corporate segment. One of the annual programs carried out by Bank BTPN's Putri Hijau Medan branch is the giving of gifts in the form of spiritual tours to a customer which is carried out annually.Spiritual tourism is tourism / recreation that focuses on the spiritual aspect (example: religion). So far, the winners have been drawn through a lottery, meaning the results were obtained randomly. There is a possibility that a customer can win twice in a row. Therefore a Decision Support System is needed to prevent this from happening so that it does not harm any party.The Descision Support System used are combination of two methods. Firstly used Multi Attribute Utility Theory (MAUT) Method which is a quantitative comparison method that usually combines measurements of the costs of different risks and benefits. This method is implemented using Rank Order Centroid (ROC) as a weighting